Effect of hybridization on properties of tamarind (Tamarindus indica L.) seed nano‐powder incorporated jute‐hemp fibers reinforced epoxy composites. Issue 12 (28th September 2021) - Sahayaraj, A. Felix; Muthukrishnan, M.; Ramesh, M.; Rajeshkumar, L.
Abstract: Current work aims to evaluate the effect of incorporating Tamarindus indica L . seed powder (TISP) and hybridization of hemp and jute natural fibers upon the characteristics of polymer nano‐composites by varying the content (in weight percentage) of both the natural fibers. TISP filled hemp fibers (HF) and jute fibers (JF) reinforced polymer composites were manufactured via compression molding technique and mechanical properties such as flexural strength and modulus, tensile strength and modulus, porosity, hardness, impact strength, and inter‐laminar shear strength (ILSS) were determined for the hybrid composites. Composites were also characterized by water absorption, Fourier transform infrared spectroscopy, and scanning electron microscopy analysis. Experimental results showcased that the tensile strength and modulus of the composites are 39.52 MPa and 2.648 GPa and the flexural strength and modulus values are of 89.62 MPa and 9.24 GPa respectively. The impact strength and ILSS values were found to be 2.35 J and 3.62 MPa. Composites containing 40 wt% JF and 10 wt% HF showcased reduced amount of void content because of the appreciable compatibility existed between matrix and the fibers. Abstract :